Analysis of Morphological and Mechanical Behaviors of Bamboo Flour Reinforced Polypropylene Composites - Bhandari, Netra L; Thomas, Sabu; Das, Chapal K; Adhikari, Rameshwar (Nepal Journal of Science and Technology, 2013)
In this paper, the bamboo flour (BF) reinforced polypropylene (PP) composites were studied with special attention to morphology of the composites and the effectiveness of chemically modified fillers to improve their mechanical properties. The composites of polypropylene with neat bamboo flour (BF) and treated bamboo flour (TBF) in different proportions were prepared by melt mixing followed by compression molding. The samples were characterized by Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), tensile testing and water absorption testing. The results show that the alkali treated BF is compatible with polypropylene matrix than the neat one as the effects are reflected in the morphological features of the composites and their tensile mechanical properties. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 95-100 DOI: http://dx.doi.org/10.3126/njst.v13i1.7447